Behavior of Molybdenum (VI) in DMDOHEMA–HDEHP/nitric acid Liquid–Liquid Extraction Systems. Issue 5 (28th July 2016) - Marie, Cécile; Vanel, Vincent; Watanabe, Sou; Duchesne, Marie-Thérèse; Zorz, Nicole; Berthon, Laurence
ABSTRACT: The EXAm (extraction of americium) process was developed for americium recycling in future nuclear fuel cycles. In this solvent extraction system, a combination of two extractants, N, N ′-dimethyl- N, N ′-dioctyl-hexylethoxy malonamide (DMDOHEMA) and di-2-ethylhexyl phosphoric acid (HDEHP), in TPH (hydrogenated tetrapropylene) is used to extract americium in the first step of the process at high acidity (HNO3 5–6 M). Americium is co-extracted with light lanthanides and other fission products like molybdenum, iron, ruthenium, etc.. Molybdenum is selectively scrubbed during the second step at low acidity using citric or glycolic acid as a buffer and complexing agent. The speciation of Mo(VI) in aqueous solutions is highly dependent on acidity and Mo concentration. In this article, a simple thermodynamical model is proposed for Mo(VI) scrubbing based on batch extraction experiments (with pH and cation concentration variations) and stoichiometries of complexes formed in the organic phase according to electrospray ionization mass spectrometry (ESI-MS) experiments and published data on Mo(VI) speciation. At high acidity ([HNO3 ] > 1 M), the MoO2 2+ species is strongly extracted by the solvent DMDOHEMA–HDEHP according to a solvate mechanism. At lower acidity ([HNO3 ] < 1 M), cation exchange mechanisms become predominant and DMDOHEMA does not participate to the extraction Mo(VI) anymore. During Mo scrubbing at pH higher than 1, the extraction of Mo as neutral species (like MoO3 ) and anionic species (like MoO4 2– ) has to be taken into account in the model to predict the "bell-shape" of Mo distribution ratio evolution as a function of pH. This model was then implemented in the PAREX simulation code developed by the CEA to build the flowsheet for the "Mo scrubbing" section of EXAm process and predict Mo concentrations profiles in batteries of mixer-settlers during pilot-scale tests.